The Oxford handbook of the corporation - Clarke, Thomas, 1950-; O'Brien, Justin (Peter Justin); O'Kelley, Charles R. (Charles Rogers), 1946- (Oxford : Oxford University Press, 2019)
This handbook assesses the contemporary relevance, purpose, and performance of the corporation. The corporation is one of the most significant, if contested, innovations in human history, and the direction and effectiveness of corporate law, corporate governance, and corporate performance are being challenged as never before. Continuously evolving, the corporation as the primary instrument for wealth generation in contemporary economies demands frequent assessment and reinterpretation. The focus of this work is the transformative impact of innovation and change upon corporate structure, purpose, and operation.
The Evolving Corporation: Economy, Law and Society / Thomas Clarke, Justin O'Brien -- Corporate Law as a Solution to Team Production Problems / Margaret M. Blair -- The Evolution of Corporate Form: From Shareholders' Property to the Corporation as Commons / Simon Deakin -- The Theory of Innovative Enterprise: Foundations of Economic Analysis / William Lazonick -- Theorizing the Corporation: Liberal, Confucian and Socialist Perspectives / Teemu Ruskola -- The Neoliberal Corporation / David Ciepley -- Finance Capitalism, the Financialised Corporation, and Countervailing Power / John W. Cioffi -- Global Corporations and Global Value Chains: The Disaggregation of Corporations? / Thomas Clarke, Martijn Boersma -- Growth Strategies of the New Multinationals / Mauro F. Guillén, Esteban García-Canal -- The Dutch East India Company: The First Corpoate Governance Debacle / Paul Frentrop -- Corporations in the Clouds? The Transformation of the Corporation in an Era of Disruptive Innovations / Danielle Logue -- Corporations, Organisation and Human Action: An Anthropological Critique of Agency Theory / Jean-François Chanlat -- The Japanese Corporation: Community, Purpose, and Strategy / Takaya Seki -- Dynamic Capabilities, the Multinational Corporation, and Capturing Co-created Value from Innovation / Christos N. Pitelis, David J. Teece -- Corporate Responsibility and the Embeded Firm: A Critical Reappraisal / Cynthia A. Williams -- Corporate Sustainability in a Fragile Planet / Suzanne Benn, Melissa Edwards -- The Changing Nature of the Corporation and the Economic Theory of the Firm / Nicolai Foss, Stefan Linder -- Transcending the Corporation: Social Enterprise, Coorperatives and Commons-based Governance / Bronwen Morgan -- Corporations as Sempiternal Legal Persons / Lynn Stout -- The English East India Company and the Company-State and the Modern Corporation: The Google of its Time? / Phili
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 11, 2019).
Keywords: Corporations